2018
DOI: 10.1139/cjss-2018-0049
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing combining green manures and pelletized manure for organic spring wheat production

Abstract: Well-planned crop rotations and targeted use of organic amendments are critical to success in organic wheat production. The impact of green manure (GMr) type, GMr termination timing, and “Acti-Sol” [pelletized dehydrated poultry manure (DPM); 5-2-3] on organic wheat productivity and quality was evaluated from 2014 to 2016 in Truro, NS, and Saint-Mathieu-de-Beloeil, QC. Crops prior to wheat were soybean or GMr of hairy vetch/oat (HVO), common vetch/oat (CVO), and red clover (RC) (NS site), and HVO, red clover/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The high soil NO 3 –N content measured at corn planting might be explained by the mineralization of shoot and root cover crop biomass during winter and in early spring (Thorup‐Kristensen et al., 2003). Decomposition of cover crop residues with low C/N ratios, as in the present study (between 10 and 16 for shoot biomass), could result in a greater decomposition rate of those residues (Singh et al., 2020) and in net mineralization as compared to that of cover crop residues with greater C/N ratio (>30) (Alam et al., 2018; Sievers & Cook, 2018). Moreover, shoot C/N ratio was inversely correlated with soil NO 3 –N content at corn planting (Pearson correlation coefficient of −0.52, P < .001; data not shown).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The high soil NO 3 –N content measured at corn planting might be explained by the mineralization of shoot and root cover crop biomass during winter and in early spring (Thorup‐Kristensen et al., 2003). Decomposition of cover crop residues with low C/N ratios, as in the present study (between 10 and 16 for shoot biomass), could result in a greater decomposition rate of those residues (Singh et al., 2020) and in net mineralization as compared to that of cover crop residues with greater C/N ratio (>30) (Alam et al., 2018; Sievers & Cook, 2018). Moreover, shoot C/N ratio was inversely correlated with soil NO 3 –N content at corn planting (Pearson correlation coefficient of −0.52, P < .001; data not shown).…”
Section: Discussionmentioning
confidence: 55%
“…For example, Alam et al. (2018) found greater N contribution from cover crops following fall rather than spring incorporation, in a clay loam. Moreover, the C/N ratio of the cover crop residues can impact the temporal synchronicity between N mineralization and N crop demand (Carr et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In Michigan, while clay content was a dominant driver of soil health, Tu et al (2021) found that crop diversification, regardless of composition-i.e., forages or cover crops, increased soil mineralizable C and aggregate stability, supporting the concept of overall spatial and temporal vegetative diversification being a key consideration. While agronomic benefits from cover crops to the following organic cash crops have been demonstrated (Alam et al, 2016(Alam et al, , 2018 their routine use varies with intensity of organic farm management. For organic farms weeds also may be a not insignificant contribution to the vegetative diversity benefiting soil health.…”
Section: Soil Organic Carbon and Soil Healthmentioning
confidence: 99%
“…Combining CGMs with pelletized PL improved organic wheat yields compared to only using CGMs in Nova Scotia and Quebec (Alam, Lynch, Tremblay, Gillis‐Madden, & Vanasse, 2018). In that study, more consistent yield improvements occurred following an oat + hairy vetch mixture than red clover, red clover + oat and oat CGM crops.…”
Section: Animal Integration Into Organic Field Crop Systemsmentioning
confidence: 99%
“…In that study, more consistent yield improvements occurred following an oat + hairy vetch mixture than red clover, red clover + oat and oat CGM crops. An application of 80 kg N ha −1 of pelletized PL could be substituted for the legume CGM crop without a change in wheat yield (Alam et al., 2018). Supplementing red clover and hairy vetch CGMs with municipal solid‐food waste composts consistently increased potato yield in a 3‐yr study conducted in Nova Scotia (Lynch et al., 2012).…”
Section: Animal Integration Into Organic Field Crop Systemsmentioning
confidence: 99%